2017
DOI: 10.1155/2017/3259357
|View full text |Cite
|
Sign up to set email alerts
|

Image Super‐Resolution Based on Sparse Representation via Direction and Edge Dictionaries

Abstract: Sparse representation has recently attracted enormous interests in the field of image super-resolution. The sparsity-based methods usually train a pair of global dictionaries. However, only a pair of global dictionaries cannot best sparsely represent different kinds of image patches, as it neglects two most important image features: edge and direction. In this paper, we propose to train two novel pairs of Direction and Edge dictionaries for super-resolution. For single-image super-resolution, the training imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…So, for the identity metrics hyper sphere space is used, for the training data set CNN used and in the same way for the feature extraction Euclidian distance is used. Zhu et al (2017) performed the scaling the images with scaling factor of 2 author has used VDSR which is based on bi cubic interpolation and then for training data set with residual learning CNN is used in Zhu et al (2017). Convergence speed is maximized and gradient clipping is used to ensure the training stability which is able to overcome the problem in SRCNN.…”
Section: B Processing Of Digital Imagementioning
confidence: 99%
“…So, for the identity metrics hyper sphere space is used, for the training data set CNN used and in the same way for the feature extraction Euclidian distance is used. Zhu et al (2017) performed the scaling the images with scaling factor of 2 author has used VDSR which is based on bi cubic interpolation and then for training data set with residual learning CNN is used in Zhu et al (2017). Convergence speed is maximized and gradient clipping is used to ensure the training stability which is able to overcome the problem in SRCNN.…”
Section: B Processing Of Digital Imagementioning
confidence: 99%
“…Sparse coding assumes the image as a sparse linear combination of elements, which can be selected from a pre-constructed and sparse enough dictionary [5]. Zhu et al [17] demonstrated an example of using sparse coding via direction and edge dictionary for image resolution. Yang et al [18,19] developed a sparse coding network to train a joint dictionary to find a highly sparse and over-complete coefficient matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A good interpolation algorithm needs to be simple and must have low complexity, so that it can easily be implemented. Many researchers [5]- [18] have proposed algorithms for upscaling digital images. Nearest neighbors, bilinear and bicubic [4] are popular and time-efficient interpolations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [16], Timofte et al [17], and Zhu et al [18] have proposed dictionary learning based image interpolation methods named Self-learning and Adaptive Sparse Representation (SL-ASR), Anchored Neighborhood Regression (ANR) and Single Image Super Resolution (SISR), respectively. SISR uses multiple dictionaries that make it far more complex method compared to ANR and SL-ASR.…”
Section: Introductionmentioning
confidence: 99%